A Naturalistic, European Multi-Center Clinical Study of Electrodermal Reactivity and Suicide Risk Among Patients With Depression - Carli, Vladimir; Hadlaczky, Gergo; Petros, Nuhamin Gebrewold; Iosue, Miriam; Zeppegno, Patrizia; Gramaglia, Carla; Amore, Mario; Baca-Garcia, Enrique; Batra, Anil; Cosman, Doina; Courtet, Philippe; Di Sciascio, Guido; et al. (Frontiers in Psychiatry, 2022)
Background: Electrodermal hyporeactivity has been proposed as a marker of suicidal risk. The EUDOR-A study investigated the prevalence of electrodermal hyporeactivity among patients with depression and its association with attempted and completed suicide. Methods: Between August 2014 and March 2016, 1,573 in- and outpatients with a primary diagnosis of depression (active or remission phase) were recruited at 15 European psychiatric centers. Each patient was followed-up for one year. Electrodermal activity was assessed at baseline with the ElectroDermal Orienting Reactivity (EDOR) Test. Data on subjects’ sociodemographic characteristics, clinical diagnoses and treatment were also collected. The severity of the depressive symptoms was assessed through the Montgomery-Asberg Depression Rating Scale. Information regarding number, time and method of suicide attempts was gathered at baseline and at the end of the one-year follow-up. The same data were collected in case of completed suicide. Results: Hyporeactive patients showed to be significantly more at risk of suicide attempt compared to reactive patients, both at baseline and follow-up. A sensitivity of 29.86% and a positive predictive value (PPV) of 46.77% were found for attempted suicide at baseline, while a sensitivity of 35.36% and a PPV of 8.92% were found for attempted suicide at follow-up. The sensitivity and PPV for completed suicide were 25.00% and 0.61% respectively. However, when controlled for suicide attempt at baseline, the association between hyporeactivity and follow-up suicide attempt was no longer significant. The low number of completed suicides did not allow any analysis.